(untitled) (Boletin Médico de Postgrado, 2023)
Cranioencephalic trauma is one of the main causes of admission to specialized health centers, so the care of the neurocritical patient is aimed at avoiding the damage caused by secondary injury caused mainly by intracranial hypertension, so there are tools such as ultrasonography of the optic nerve that help reduce the time of action for the treatment of the patient. The objective of this study was to determine the sensitivity, specificity and predictive values of the measurement of the optic nerve sheath diameter measured by ultrasound for the detection of intracranial hypertension in patients with cranioencephalic trauma at the Hospital Central Universitario Dr. Antonio María Pineda. A 7.5 Hz transducer was used and measurements were taken once per shift, recording the measurement in millimeters. Thirty-two total measurements were taken in 16 patients (11 males, 5 females) with an average age of 23 years and moderate cranioencephalic trauma. It was possible to establish the cut-off of 5.3 mm for the diagnosis of intracranial hypertension with a sensitivity of 100% and specificity of 90.4%. It was proved that there is a directly proportional correlation between the increase of the optic nerve sheath diameter and intracranial hypertension (p = 0.001), being the measurement of the optic nerve sheath a useful tool for the evaluation of intracranial hypertension in the patient with cranioencephalic trauma in our emergency room.